2017
DOI: 10.1186/s13287-017-0486-5
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells alleviate Japanese encephalitis virus-induced neuroinflammation and mortality

Abstract: BackgroundJapanese encephalitis virus (JEV) is the leading cause of viral encephalitis in Asia. Japanese encephalitis (JE) caused by JEV is characterized by extensive inflammatory cytokine secretion, microglia activation, blood-brain barrier (BBB) breakdown, and neuronal death, all of which contribute to the vicious cycle of inflammatory damage. There are currently no effective treatments for JE. Mesenchymal stem cells (MSCs) have been demonstrated to have a therapeutic effect on many central nervous system (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
0
21
0
1
Order By: Relevance
“…The activation of microglia is considered to be the cardinal hallmark of neuroinflammation, and is characterized by its morphological change to M1 phenotype, as well as secretion of a series of proinflammatory mediators. M1 activation of microglia followed by neuroinflammation is a common feature of Japanese encephalitis (36). Following JEV invasion, glial cells elicit immune response against pathogens; however, viral replication within microglia results in bystander neuronal death by secretion of inflammatory mediators (4).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of microglia is considered to be the cardinal hallmark of neuroinflammation, and is characterized by its morphological change to M1 phenotype, as well as secretion of a series of proinflammatory mediators. M1 activation of microglia followed by neuroinflammation is a common feature of Japanese encephalitis (36). Following JEV invasion, glial cells elicit immune response against pathogens; however, viral replication within microglia results in bystander neuronal death by secretion of inflammatory mediators (4).…”
Section: Discussionmentioning
confidence: 99%
“…Intracerebral inflammation can cause death in PD patients [ 31 , 32 ]. The mortality of LPS-induced PD mice was not reported in previous studies, but we demonstrated for the first time that 10, 20, and 40 mg/kg Rg1 treatment decreased mouse mortality by 12.5%, 25.7%, and 25.7%, respectively, compared to that in the LPS-only group.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mice (n=5) from each group were euthanized by cervical dislocation, on the 7 th , 14 th days after starting treatment administration. Such times were proven to be effective for successful testing of the therapeutic MSCs effect on the infected mice [22].…”
Section: Discussionmentioning
confidence: 99%